Effect of Plant Density and Fertilizer Management Practices on Yield of Spring Maize - Mandal, Binod Kumar; Yadav, Pankaj Kumar; Marahatta, Santosh; Bhujel, Prabina (Agronomy Journal of Nepal, 2023)
The grain yield of maize is lowered by an insufficient plant population and an unbalanced fertilizer application. An experiment was carried out in the spring to address these problems. The treatments were set up in a split-plot design with three replications and included factorial combinations of three planting densities and four fertilizer levels: 120:60:40 kg N, P2O5, K2O ha-1, 120% RBR, 150% RBR, and site-specific nutrient management (SSNM), 140:40:40 kg N, P2O5, K2O ha-1. Both the barrenness and sterility percentages were higher (p